2012
DOI: 10.5433/1679-0367.2012v33n1p97
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos da invasão por Panicum maximum Jacq. e do seu controle manual sobre a regeneração de plantas lenhosas no sub-bosque de um reflorestamento

Abstract: Responsáveis por perdas anuais consideráveis na biodiversidade dos ecossistemas naturais, as espécies exóticas invasoras causam sérios problemas à conservação, levando muitas espécies à extinção local. Este estudo analisou o efeito da cobertura de capim-colonião (Panicum maximum Jacq.) no sub-bosque de um reflorestamento dominado há mais de 17 anos por essa gramínea exótica invasora, pois resultados preliminares apontam-na como barreira para o estabelecimento de espécies nativas. Neste estudo, foram implantada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 11 publications
0
3
0
7
Order By: Relevance
“…While these results suggest that manual weeding is efficient in controlling Guinea-grass, thereby enhancing native plant development (see García-Orth and Martínez-Ramos, 2011), this technique should be used at a small-scale or at sites that require rapid control (Mantoani et al, 2012), due to its high cost (see Sampaio et al, 2007).…”
Section: Regeneration Responsesmentioning
confidence: 93%
See 1 more Smart Citation
“…While these results suggest that manual weeding is efficient in controlling Guinea-grass, thereby enhancing native plant development (see García-Orth and Martínez-Ramos, 2011), this technique should be used at a small-scale or at sites that require rapid control (Mantoani et al, 2012), due to its high cost (see Sampaio et al, 2007).…”
Section: Regeneration Responsesmentioning
confidence: 93%
“…These species were selected for their wood properties and, unfortunately, are all deciduous, with low foliage density in their canopies and abiotic seed dispersal. These features were reported to be possible causes of both grass invasion and slow native species colonization (Barbosa, 2006;Mantoani et al, 2012). After 20 years, the site is still in an early stage of ecological succession, with the understory dominated by M. maximus, despite being adjacent to a mature forest.…”
Section: Study Areamentioning
confidence: 96%
“…These authors observed an increase of 20% in the density of species and 48% in the coverage by native species in an area without forage grass control. In addition, a negative correlation has been found between the dominance of grasses and abundance and richness of native species, caused by high competition for luminosity, water and nutrients (VIDRA;SHEAR;STUCKY, 2007;MANTOANI et al, 2012;SIMMONS et al, 2016). In view of this, it is inferred that with the removal of grasses, the germination and survival rates of native species will, according to Chazdon (2012) and Fragoso et al (2017), likely increase and reduce the time taken for ecological succession.…”
Section: Resultsmentioning
confidence: 99%
“…Entretanto, para essas variáveis a presença de P. maximum, B. decumbens, U. brizantha e C. echinatus influenciou o crescimento da P. dubium (Tabela 3), promovendo os menores incrementos de biomassa. Segundo Mantoani et al (2012), o capim-colonião (Panicum maximum Jacq.) prejudica significativamente a BIOFIX Scientific Journal v. 4 n. 1 p. 153-159 2019 Menezes, E. S. et al…”
Section: Resultsunclassified